IPTEKS PERENCANAAN LABA KONTRIBUSI PADA USAHA MANUFAKTUR - Budiarso, Novi Swandari; Pontoh, Winston (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2020)
The manufacturing firms have implicit and explicit goals and objectives. In order to achieve these goal and objective then manager needs accounting information. The accounting information created and used by management is intended primarily for planning and control decisions. One of the accounting information is cost accounting that can be used as a tool for planning the profit as the objective of the companies. Manufacturing costs are identified as variable costs or fixed costs under cost behavior analysis. Regression analysis is the one of the cost estimation methods in term to estimate the fixed costs and variable costs where the results of estimation are used to calculate the contribution margin.